Cantidades y formas de fósforo en diez suelos altamente temperizados de Puerto Rico - Fassbender, H.W; Beinroth, F.H; Sarmiento, L.S (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
Amounts and forms of P were determined in sixty soil samples from profiles - one Inceptisol, four Ultisols and five Oxisols of Puerto Rico. Samples of one Oxisol and one Ultisol contain relatively large quantities of total P in all horizons, averaging 1,448 and 774 mg/kg soil, respectively. In other soils, the mean of total P values ranges from 177 to 371 mg/kg soil. Calcium and aluminum phosphates amount to less than 4 per cent of total P in all samples. Iron phosphates are the dominant inorganic forms of P in all horizons of these soils. Content of occluded P greatly exceeds the order P forms. For the A, B and C horizons of the Inceptisol and the Ultisols, occluded P accounts for 47, 69 and 76 per cent of total P, respectively. The corresponding values for the Oxisols are 40, 69 and 87 per cent. For the soils studied no relationship between the forms of P and their state nedogenetic evolution could be found.